2005
DOI: 10.1007/s10533-005-6897-x
|View full text |Cite
|
Sign up to set email alerts
|

Export of DOM from Boreal Catchments: Impacts of Land Use Cover and Climate

Abstract: Dissolved organic matter (DOM) is an important fraction in carbon (C) and nutrient budgets for aquatic ecosystems and can have broad effects on food webs and nutrient cycling. To look at the role land use cover and climate might play in DOM transport from the boreal region, the export of total organic carbon (TOC), total organic nitrogen (TON) and dissolved organic phosphorus (DOP) was estimated for Finnish main rivers and their sub-catchments, altogether 86 catchments, situated between latitudes 60°N and 69°N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
200
4
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(226 citation statements)
references
References 46 publications
20
200
4
2
Order By: Relevance
“…Collier et al (1989) and Moore & Jackson (1989) examined DoC concentrations and fluxes in Westland (South Island) catchments containing Pakihi poorly drained soils, noting high DoC concentrations and export (30 to 38 mg litre -1 and 31 to 44 g m -2 yr -1 , respectively) and an increase in export with catchment drainage for forestry, in contrast to export of 8 to 21 g m -2 yr -1 in nearby upland forested and harvested sites (Moore 1989). in the Northern Hemisphere, several studies have recorded high DoC concentrations within peat porewaters and the concentration in streams is often closely related to the proportion of peatland within the catchment (e.g., eckhardt & Moore 1990;Mattson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Collier et al (1989) and Moore & Jackson (1989) examined DoC concentrations and fluxes in Westland (South Island) catchments containing Pakihi poorly drained soils, noting high DoC concentrations and export (30 to 38 mg litre -1 and 31 to 44 g m -2 yr -1 , respectively) and an increase in export with catchment drainage for forestry, in contrast to export of 8 to 21 g m -2 yr -1 in nearby upland forested and harvested sites (Moore 1989). in the Northern Hemisphere, several studies have recorded high DoC concentrations within peat porewaters and the concentration in streams is often closely related to the proportion of peatland within the catchment (e.g., eckhardt & Moore 1990;Mattson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The DON predictions, in turn, were only satisfactory. The catchments with the highest peatland proportion had the highest TOC, DON and DOP export loads and modelled and measured concentrations, which is a typical observation in boreal and temperate regions (Dillon and Molot 1997;Pellerin et al 2004;Mattsson et al 2005;Williams et al 2005;Kortelainen et al 2006). DOM exports are large because peatlands are in close hydrological contact with receiving watercourses, peat C storage is large, organic matter decomposition is incomplete due to the anaerobic conditions, and the peat contains few compounds that can retain C such as iron and aluminium (Domisch et al 2000;Kalbitz et al 2000;Freeman et al 2001).…”
Section: Discussionmentioning
confidence: 81%
“…In addition to low peatland percentage, the catchments of the lakes 9-12 also contained agricultural land (3.5-17 % of the area). The C:N ratio of leached organic matter is typically lower in agricultural than peatland dominated catchments (Mattsson et al 2005), which may also increase the decomposition of organic matter and result in lower TOC, DON and DOP concentrations. Furthermore, it has been found that TOC, DON and DOP concentrations and export decrease with increasing percentage of lakes in the catchment areas (Mattsson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations